2017
DOI: 10.1097/igc.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Predicting Overall Survival in Operable Cervical Cancer Patients

Abstract: We developed a novel nomogram that can provide prediction of OS for patients with early stage cervical cancer individually. Furthermore, studies are required to validate whether it can be applied to other cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
3
7
0
3
Order By: Relevance
“…Alb is closely related to nutritional status in patients, which is a good indicator of immune status. Zheng found that hypoalbuminemia was associated with poor survival in 798 patients with early-stage cervical cancer [31], which was also observed in our study. Additionally, the SIS was also significantly influenced by prognosis when stratified by FIGO stage.…”
Section: Discussionsupporting
confidence: 89%
“…Alb is closely related to nutritional status in patients, which is a good indicator of immune status. Zheng found that hypoalbuminemia was associated with poor survival in 798 patients with early-stage cervical cancer [31], which was also observed in our study. Additionally, the SIS was also significantly influenced by prognosis when stratified by FIGO stage.…”
Section: Discussionsupporting
confidence: 89%
“…Alb is closely related to nutritional status in patients, which is a good indicator of immune status. Zheng found that hypoalbuminemia was associated with poor survival in 798 patients with early-stage cervical cancer [29], which was also observed in our study. Additionally, the SIS was also signi cantly in uenced by prognosis when strati ed by FIGO stage.…”
Section: Discussionsupporting
confidence: 89%
“…A 3 éves túlélés a mGPS 0., 1. és 2. csoportjában 92%, 71% és 72% (p = 0,0035) volt [30]. Reszekábilis méhnyakrákban (n = 795) a szérumalbuminszint (más faktorok mellett, mint a BMI, vérlemezkeszám, fehérvérsejtszám, a daganat differenciáltsági foka és a kismedencei nyirokcsomóstatus) az OS független prognosztikai faktorának bizonyult (p<0,05) [31]. Epithelialis ovarium carcinoma (n = 213) minden stádiumában rosszabb túlélés társult (p<0,001) az alacsony albuminszinttel (≤35 g/l) [32] -ezt a tényt más szerzők korábban már prognosztikai modellekkel is leírták [33].…”
Section: Eredményekunclassified
“…A szerzők javasolták, hogy a műtét utáni albuminszint normális tartományban tartásához (≥35 g/l) a preoperatíve mért <45 g/l albuminszint esetén táplálásterápia bevezetését tartották szükségesnek [71]. Figyelemre méltó, hogy lokalizált rosszindulatú daganatos betegségekben a normális BMI-érték melletti alacsony albuminszint rossz prognózist vetít előre, míg a BMI-értéknek az esetek nagyobb részében nincs prognosztikus értéke [25,31,32,34,37]. Gyomorrákban (n = 830) a kemoterápiás kezelés alatt alkalmazott táplá-lásterápia azoknál a pácienseknél jelentett túlélési előnyt, akiknél a kiindulási tápláltsági kockázatszűrés (NRS) pontszáma <3 volt (átlagos túlélés 31,9 vs. 25,7 hó; p<0,001).…”
Section: öSszefoglaló Közleményunclassified